Heart rate variability in patients with chronic rheumatic heart disease - V. S. Petrov (Архивъ внутренней медицины)
Objective. Evaluation of heart rate variability in patients with rheumatic heart disease.Material and methods. The study enrolled 230 patients, of whom 156 patients with mitral stenosis (CRHD), 36 patients with mitral valve regurgitation, and 38 patients with acquired aortic stenosis were selected. CHF functional class was determined using a 6-minute walk test according to the standard method; there were no patients with FC IV. HRV values were obtained using the Kardiotekhnika-04-3R (M) cardiorespiratory monitor with an estimation of time domain and frequency domain.Results. The CRHD patients had lower HRV indicators in the time (SDNN - 126.38 ms, SDANN - 112.07 ms, RMSSD - 32.79 ms) and frequency domain (VLF - 2,098.59 ms2; LF - 865.39 ms2, HF - 323.48 ms2) compared with patients with mitral valve regurgitation and aortic stenosis. Evaluation of HRV within patients with CRHD, depending on the presence or absence of combined mitral-aortic stenosis, did not show differences in the general and sympathetic tone of the ANS. In patients with combined mitral-aortic stenosis, only a decrease in parasympathetic tone was revealed: RMSSD - 31.18 ms, HF - 286.36 ms2. Stratification of patients according to FC CHF showed an increase in parasympathetic tone: RMSSD was 26.67 ms for FC I and 43.69 ms for FC III; HF was 254.67 ms2 for FC I and 541.23 ms2 for FC III. The sympathetic and general tone of the ANS was minimal in patients with FC II CHF. A study of the change of indicators over 5 years did not demonstrate a significant increase in the time domain, and the main indicators of the frequency domain decreased significantly: VLF from (1,882.73 ± 119.48) to (1,603.54 ± 99.22) ms2; HF from (334.34 ± 33.13) to (252.87 ± 17.84) ms2, LF from (819.48 ± 94.41) to (647.01 ± 42.50) ms2. A decrease in the frequency domain was also observed when comparing the HRV results of survived and deceased patients.Conclusions. The patients with CRHD had lower values of the ANS tone in comparison with patients with other acquired heart valve disease. The smallest values of the general tone of the ANS and SNS were observed in those studied with CRHD with FC II CHF, and the activity of the PNS was maximum at FC III. After 5 years of follow-up, only the frequency indices of HRV were significantly reduced.